Evaluation of Internal Control in Inventory Management to Improve Effectiveness in Inventory Management (Case Study at Oharang Restaurant Cimahi Branch) - Tobing, Angelique Ruth Tiurmauli; Monica Paramita Ratna Putri Dewi (Universitas Mohammad Husni Thamrin, 2026)
The food and beverage industry in Indonesia is growing rapidly, increasing competition and requiring restaurants to manage data appropriately, especially in inventory management as a crucial asset that supports smooth operations. Poorly managed inventory risks understocking or overstocking, necessitating adequate internal controls. This study aims to evaluate the effectiveness of internal controls in inventory management at the Oharang Restaurant, Cimahi Branch, using the COSO Enterprise Risk Management (ERM) framework and to provide recommendations for improvement. The research method used is descriptive analytical with a qualitative approach through primary and secondary data collection. Primary data were obtained through semi-structured interviews with the owner, manager, supervisor, and staff, as well as direct observation, while secondary data were obtained through inventory report documentation, company documents, and organizational structures. The results of the study indicate that internal controls are not fully adequate, especially in the control activities component, which includes weaknesses in the separation of functions, completeness of transaction documentation, authorization formalities, and inventory recording. Based on these findings, recommendations proposed include adding operational supervisors, preparing more detailed job descriptions, and implementing standard documents such as purchase orders, receiving reports, material requisitions, and stock cards to strengthen internal controls and improve the effectiveness of inventory management on an ongoing basis. It is hoped that the research findings can be the basis for improvements that support operational effectiveness and smoothness.